2013
DOI: 10.1016/j.wocn.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Computational simulation of CV combination preferences in babbling

Abstract: There is a tendency for spoken consonant-vowel (CV) syllables, in babbling in particular, to show preferred combinations: labial consonants with central vowels, alveolars with front, and velars with back. This pattern was first described by MacNeilage and Davis, who found the evidence compatible with their “frame-then-content” (F/C) model. F/C postulates that CV syllables in babbling are produced with no control of the tongue (and therefore effectively random tongue positions) but systematic oscillation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…However, our modeling results show that there is systematicity in the off-diagonals that is well-predicted by Articulatory Phonology (AP), which can calculate the synergy between any two phones. Our modeling of F/C did not support the assumptions of that model (Nam, Giulivi, Goldstein, Levitt, & Whalen, submitted). Because of this systematicity, we will expand the investigation to the off-diagonals here.…”
Section: Introductioncontrasting
confidence: 83%
“…However, our modeling results show that there is systematicity in the off-diagonals that is well-predicted by Articulatory Phonology (AP), which can calculate the synergy between any two phones. Our modeling of F/C did not support the assumptions of that model (Nam, Giulivi, Goldstein, Levitt, & Whalen, submitted). Because of this systematicity, we will expand the investigation to the off-diagonals here.…”
Section: Introductioncontrasting
confidence: 83%
“…So far these weights have been gleaned from subjective evaluation of the results of speech production experiments and through back-fitting of the weight parameters based on speech synthesis using the task dynamic simulator TADA (Task Dynamic Toolkit) (Nam et al, 2004). Another measure of synergy has recently been explored in simulating results from babbling, namely, that the distance between the target positions of different segments can be converted directly into a synergy measure (Nam et al, 2013).…”
Section: Measuring Synergymentioning
confidence: 99%
“…It seems likely, therefore, that we will soon be able to exploit such databases also for other purposes, such as measuring the formants in vowel-like portions of the infants' vocalizations to replicate and extend several landmark studies of cross-language differences in vowel development (de Boysson-Bardies et al, 1989; Rvachew et al, 2006), or basing a more elaborated annotation method on the automatic tagging of the vocalization type. For example, imagine a set of modeling studies that extends Serkhane et al (2007) versus Nam et al (2013) to phonetically transcribed canonical babble produced by infants acquiring languages other than American English. The data might be got from daylong recordings gathered for other purposes, such as Canault et al (2015), by picking out just the vocalizations that have been identified as canonical babble in the recordings made between 6 and 12 months, using these as stimuli in a web-based experiment where several adults imitate each vocalization, and then applying standard ASR to the adult imitations to make a consensus phonetic transcription.…”
Section: Databases Of Infant-directed Speech and Infant “Speech”mentioning
confidence: 99%